Konselor, manajemen stres dan konseling karier - Renatha Ernawati (1st ASEAN School Counselor Conference on Innovation and Creativity in Counseling)
Today there is an increasing emphasis on employees worjing well, and working on it with job security can never be considered to happen by inevitable change is an ever-present problem, in good mental and physical conditions for the first clien The career counselor is very helpful in identifying whether or not it is induced stress is in fact related to issues with a career counseling approach. Make a choice of work by a clear illustration of strength and rationality. Considerations about external power surnber such as can contribute to sress management, but life will not be the only factor to be considered. The more generic for stress management approach a keyword counselor stress management.